(3JdbjM aghe Cgd GdCKQI aj Yjhf GdJGQjN hGdSjQIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3GHQGgje Hf eMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3GdMeO ddg Ydi EMSGfg hCaVGdg gPG cJGH PcQ ajg GdJhGQjN hGdSjQ afhfG PcQ Chd GdeNdhbGJ s
(3BNQgG (B:s
(3GdWHbI GdQGHYI YTQ (B: (3cGf GdNdjaI Ydi QCS GdSJjf hGdNeSeGFI GdeSJfLO HGddg BNQ GdcJGH hGdMeO ddg Ydi cd MGd s
(3GdfSNI HgG MhGTs
(3HBNQgG eYGQVI HfSNI GdMGaX TeS GdOjf Hf Ndjd GdOeTbi heYXegG HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJGQjNs